2017
DOI: 10.1093/jac/dkx345
|View full text |Cite
|
Sign up to set email alerts
|

Envelope proteome changes driven by RamA overproduction in Klebsiella pneumoniae that enhance acquired β-lactam resistance

Abstract: Whilst RamA is not a key mediator of antibiotic resistance in K. pneumoniae on its own, it is potentially important for enhancing the spectrum of acquired β-lactamase-mediated β-lactam resistance. LC-MS/MS proteomics analysis has revealed that this enhancement is achieved predominantly through activation of efflux pump production.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 29 publications
4
33
0
Order By: Relevance
“…Fluorescent dye accumulation assays revealed that the shape of the dye accumulation curve for representative rule 15 clinical isolates KP7 and KP8 ( Fig. 1A and B) was like that seen previously upon micF overexpression in Ecl8, i.e., causing reduced OmpF (OmpK35) porin production (26). Porin reduction retards the entry of the dye but does not prevent the accumulation of the dye over time.…”
Section: Resultssupporting
confidence: 64%
See 3 more Smart Citations
“…Fluorescent dye accumulation assays revealed that the shape of the dye accumulation curve for representative rule 15 clinical isolates KP7 and KP8 ( Fig. 1A and B) was like that seen previously upon micF overexpression in Ecl8, i.e., causing reduced OmpF (OmpK35) porin production (26). Porin reduction retards the entry of the dye but does not prevent the accumulation of the dye over time.…”
Section: Resultssupporting
confidence: 64%
“…Porin reduction retards the entry of the dye but does not prevent the accumulation of the dye over time. This phenotype is in stark contrast to efflux-mediated reduced envelope permeability, which gives a persistent level of reduced dye accumulation, as seen in the Ecl8 ΔramR mutant previously (26) and, for example, in clinical isolate KP21, which has a ramR mutation and overproduces AcrAB-TolC (Table 2 and Fig. 1C).…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Mutations in the repressor gene ramR can upregulate expression of the positive activator RamA, which in turn upregulates expression of the acrAB-tolC and oqxAB-tolC efflux pump genes along with other regulatory changes; ramR mutations have also been identified in clinical isolates (22,(28)(29)(30)(31)(32). RamAmediated upregulation of AcrAB-TolC and/or OqxAB-TolC has also been reported to decrease susceptibility to a range of ␤-lactams, including ATM (33). Furthermore, NB29002-JBA0001 was also less susceptible to TGC and CHL, known substrates of AcrAB-TolC that are structurally unrelated to LYS228.…”
Section: Figmentioning
confidence: 99%